Microstructural Development in a Laser-Remelted Al-Zn-Si-Mg Coating. Issue 1 (December 2017) - Godec, M.; Podgornik, B.; Nolan, D.
Abstract In the last five decades, there has been intense development in the field of Zn-Al galvanic coating modification. Recently, Mg was added to improve corrosion properties. Further improvements to the coating are possible with additional laser surface treatment. In this article, we focus on remelting the Al-Zn-Mg-Si layer, using a diode laser with a wide-beam format, concentrating on the microstructure development during extreme cooling rates. Laser remelting of the Al-Zn-Mg-Si coating and rapid self-quenching produces a finer grain size, and a microstructure that is substantially refined and homogenized with respect to the phase distribution. Using EBSD results, we are able to understand microstructure modification. The laser modified coating has some porosity and intergranular cracking which are difficult to avoid, however this does not seem to be detrimental to mechanical properties, such as ductility on bending. The newly developed technology has a high potential for improved corrosion performance due to highly refined microstructure.